The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/08927014.2017.1286649
|View full text |Cite
|
Sign up to set email alerts
|

The response of Escherichia coli biofilm to salicylic acid

Abstract: In this research, salicylic acid is proposed as an alternative biocide-free agent suitable for a preventive or integrative anti-biofilm approach. Salicylic acid has been proved to: (1) reduce bacterial adhesion up to 68.1 ± 5.6%; (2) affect biofilm structural development, reducing viable biomass by 97.0 ± 0.7% and extracellular proteins and polysaccharides by 83.9 ± 2.5% and 49.5 ± 5.5% respectively; and (3) promote biofilm detachment 3.4 ± 0.6-fold. Moreover, salicylic acid treated biofilm showed an increased… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
43
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
3
2

Relationship

2
3

Authors

Journals

citations
Cited by 32 publications
(48 citation statements)
references
References 55 publications
0
43
0
1
Order By: Relevance
“…It has been found that ZA targets key step involved in E. coli biofilm formation by modulating the threshold level of the autoinducer‐2 signal and inducing a hypermotile phenotype unable to firmly adhere on surfaces . Conversely, SA anti‐biofilm action involves multiple complex mechanisms affecting cells adhesion, extracellular matrix production, the quorum sensing indole balance and bacterial motility also making biofilm more prone to be dethatched from the surface . It has been speculated that both molecules exploit their anti‐biofilm performances by a ROS‐based mechanism that modulates the activity of some proteins resulting in a decrease of biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…It has been found that ZA targets key step involved in E. coli biofilm formation by modulating the threshold level of the autoinducer‐2 signal and inducing a hypermotile phenotype unable to firmly adhere on surfaces . Conversely, SA anti‐biofilm action involves multiple complex mechanisms affecting cells adhesion, extracellular matrix production, the quorum sensing indole balance and bacterial motility also making biofilm more prone to be dethatched from the surface . It has been speculated that both molecules exploit their anti‐biofilm performances by a ROS‐based mechanism that modulates the activity of some proteins resulting in a decrease of biofilm formation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, it has been found that E. coli proteins targeted by ZA and SA are widespread with a high percentage of identity in a wide range of microorganisms, included several E. coli pathogenic stains and bacteria involved in serious disease. Thus, it is possible that LDPE‐CA and LDPE‐ZA could exert their activity also against other bacterial strains.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations